IgE allergy diagnostics and other relevant tests in allergy, a World Allergy Organization position paper - Ansotegui, Ignacio J.; Melioli, Giovanni; Canonica, Giorgio Walter; Caraballo, Luis; Villa, Elisa; Ebisawa, Motohiro; Passalacqua, Giovanni; Savi, Eleonora; Ebo, Didier; Gómez, R. Maximiliano; Luengo Sánchez, Olga; Oppenheimer, John J.; et al. (The World Allergy Organization journal, 2020)
Currently, testing for immunoglobulin E (IgE) sensitization is the cornerstone of diagnostic evaluation in suspected allergic conditions. This review provides a thorough and updated critical appraisal of the most frequently used diagnostic tests, both in vivo and in vitro. It discusses skin tests, challenges, and serological and cellular in vitro tests, and provides an overview of indications, advantages and disadvantages of each in conditions such as respiratory, food, venom, drug, and occupational allergy. Skin prick testing remains the first line approach in most instances; the added value of serum specific IgE to whole allergen extracts or components, as well as the role of basophil activation tests, is evaluated. Unproven, non-validated, diagnostic tests are also discussed. Throughout the review, the reader must bear in mind the relevance of differentiating between sensitization and allergy; the latter entails not only allergic sensitization, but also clinically relevant symptoms triggered by the culprit allergen.